Isolation and characterization of potential amylolytic, proteolytic, gelatinolytic and chitinolytic properties in bacterial antagonists obtained from chilli plants (Colletotrichum spp.) - Tarigan Rasiska; Lisnawita Lisnawita; Tantawi A.R.; Hermanto Catur (BIO Web of Conferences)
Several bacteria are found to be potential as antagonists due to their capacity in producing extracellular enzymes amylase, protease, gelatinase, cellulose and chitinase. In this research, we collected bacteria from both healthy and anthracnose-infecting chili plants (root, stem and leaf). The results revealed that 27 bacterial isolates are non-pathogenic and non-hemolytic to plants, which are 10 bacteria isolated from roots, 8 bacteria isolated from leaves, 7 bacteria isolated from stems and 2 bacteria isolated from fruits. Morphology identification showed that most of non-pathogenic bacteria are circular, irregular and punctiform, with elevation flat, raised and umbonate. White and milky bacteria are dominant, with varied opacity (transparent, translucent and opaque) and textures (slimy, mucoid, shiny and dry). Enzymatic activity test revealed 11 isolates produced protease, amylase and chitinase enzymes (isolates 11, 34, 42, 48, 111,118, 139, 188, 215, 216 and 218).